Analysis of Self Efficiacy, Internal Locus of Control and External Locus of Control on the Performance of Educational Staff Employees at Madrasah Tsanawiyah Negeri 3 Kediri - Andi Wicaksono, Mohammad; Kusumanintyas, Dian (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to examine the effects of self-efficacy, internal locus of control, and external locus of control on educators' performance. Design/Methode/Approach: A quantitative approach was utilized, employing a survey method through questionnaire distribution to educators. The data were analyzed using multiple linear regression to assess the relationship between independent and dependent variables. Research Finding: The results indicate that self-efficacy, internal locus of control, and external locus of control significantly influence educators' performance. Among these factors, self-efficacy has the most substantial impact. This study contributes to the theoretical understanding of psychological aspects, particularly locus of control, in shaping educators' performance. Its originality lies in integrating self-efficacy, internal locus of control, and external locus of control within the context of educators, yielding insights that differ from previous research. This study offers new perspectives on these variables to enhance individual performance. Theoretical contribution/Originality: This research makes a theoretical contribution by expanding the understanding of psychological factors, such as locus of control, that contribute to the performance of educators. The novelty of this study lies in the combination of analysis of variables of self efficacy, internal locus of control, and external locus of control in the context of educators who give different results from previous researchers. This illustrates that this research will provide the latest insight into this variable to make a person's performance even better. Practitionel/Policy implication: The findings provide valuable insights for educational institution administrators in improving educator performance. Enhancing self-efficacy and implementing management strategies that consider locus of control can lead to better outcomes. Research limitations: This study focuses solely on three primary variables, excluding other influential factors such as job experience, leadership style, or organizational culture. Additionally, the use of questionnaires as the data collection method presents potential biases, including inaccuracies or lack of honesty in responses